2014
DOI: 10.1016/j.bbmt.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Varicella-Zoster Vaccine in Hematopoietic Stem Cell Transplantation Recipients

Abstract: Hematopoietic stem cell transplantation (HSCT) recipients are at risk for varicella-zoster virus (VZV) reactivation. Vaccination may help restore VZV immunity; however, the available live attenuated VZV vaccine (Zostavax) is contraindicated in immunocompromised hosts. We report our experience with using a single dose of VZV vaccine in 110 adult autologous and allogeneic HSCT recipients who were about 2 years after transplantation, free of graft-versus-host disease, and not receiving immunosuppression. One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 22 publications
1
29
0
2
Order By: Relevance
“…Hata et al reported that inactivated varicella vaccine significantly reduced risk of clinical VZV disease in patients who underwent auto-HCT [19]. Issa et al reported that 110 adult autologous and allogeneic HCT recipients used the live attenuated varicella vaccine, and it was safe, although a longer follow-up is warranted to evaluate its clinical efficacy [20]. We are also conducting a clinical trial to evaluate the safety, efficacy, and immunogenicity of the live attenuated varicella vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Hata et al reported that inactivated varicella vaccine significantly reduced risk of clinical VZV disease in patients who underwent auto-HCT [19]. Issa et al reported that 110 adult autologous and allogeneic HCT recipients used the live attenuated varicella vaccine, and it was safe, although a longer follow-up is warranted to evaluate its clinical efficacy [20]. We are also conducting a clinical trial to evaluate the safety, efficacy, and immunogenicity of the live attenuated varicella vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data on the safety and efficacy of live-attenuated varicella vaccines in allo-HSCT recipients are limited (14,15), no serious adverse events were reported in a previous study involving 110 adult allo-HSCT patients (16). Thus, the guidelines recommend varicella vaccination at 2 or more years after transplantation in allo-HSCT patients without active chronic GVHD or ongoing immunosuppressive therapy (evidenced-based rating: CIII) (17,18).…”
Section: Discussionmentioning
confidence: 96%
“…113 In immunosuppressed elderly persons with leukaemia, lymphoma and HIV, or during and for 6 months after a prescription for an immunosuppressive drug, including oral corticosteroids, as well as in patients with rheumatoid arthritis, psoriatic arthritis, psoriasis, spondylitis and inflammatory bowel disease, the ZLAV vaccine has been shown to be safe and effective in reducing the incidence of zoster, whereas in patients with haematological malignancies, ZLAV was safe and compared to no vaccination, may reduce herpes zoster, but without a statistically significant difference. 115 However, ZLAV is actually contraindicated in immunocompromised persons and only those with leukaemia in remission and those who have not received chemotherapy or radiation for at least 3 months may receive ZLAV. 113 The adjuvanted VZV gE subunit vaccine will be the vaccine of choice for immunocompromised persons.…”
Section: Varicella (V) and Zoster Vaccinationmentioning
confidence: 99%